0
$\begingroup$

I already asked a similar question on another post: Solving non linear differential equation.

\begin{align} &a \ \ddot{u}+b\ \left(\dot{u}\right)^2 +\dot{u}+\dot{u}\ c\ e^{u}+e^u-e^{2u}+1=0 \end{align}

How to solve this equation and what's the general solution? I tried to multiply by $\dot{u}$ but I was not able to solve the equation. Any suggestions?

Thanks.

$\endgroup$
  • $\begingroup$ What is the independent variable of this ODE? $\endgroup$ – doraemonpaul Jul 6 '12 at 21:39
  • $\begingroup$ $u=u(t)$, t is the independent variable $\endgroup$ – Mark Jul 6 '12 at 22:10
0
$\begingroup$

$a~\ddot{u}+b\left(\dot{u}\right)^2+\dot{u}+\dot{u}ce^u+e^u-e^{2u}+1=0$

$a\dfrac{d^2u}{dt^2}+b\left(\dfrac{du}{dt}\right)^2+(ce^u+1)\dfrac{du}{dt}+e^u-e^{2u}+1=0$

Case $1$: $a\neq0$

This belongs to an ODE of the form http://eqworld.ipmnet.ru/en/solutions/ode/ode0508.pdf

Let $v=\dfrac{du}{dt}$ ,

Then $\dfrac{d^2u}{dt^2}=\dfrac{dv}{dt}=\dfrac{dv}{du}\dfrac{du}{dt}=v\dfrac{dv}{du}$

$\therefore av\dfrac{dv}{du}+bv^2+(ce^u+1)v+e^u-e^{2u}+1=0$

$av\dfrac{dv}{du}=-bv^2-(ce^u+1)v+e^{2u}-e^u-1$

$v\dfrac{dv}{du}=-\dfrac{bv^2}{a}-\dfrac{(ce^u+1)v}{a}+\dfrac{e^{2u}-e^u-1}{a}$

This belongs to an Abel equation of the second kind.

In fact, all Abel equation of the second kind can be transformed into Abel equation of the first kind.

Let $v=\dfrac{1}{w}$,

Then $\dfrac{dv}{du}=-\dfrac{1}{w^2}\dfrac{dw}{du}$

$\therefore-\dfrac{1}{w^3}\dfrac{dw}{du}=-\dfrac{b}{aw^2}-\dfrac{ce^u+1}{aw}+\dfrac{e^{2u}-e^u-1}{a}$

$\dfrac{dw}{du}=-\dfrac{(e^{2u}-e^u-1)w^3}{a}+\dfrac{(ce^u+1)w^2}{a}+\dfrac{bw}{a}$

Please follow the method in http://www.hindawi.com/journals/ijmms/2011/387429/#sec2

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.